Microvascular anastomotic coupler application learning curve: A curriculum supporting further deliberate practice in ex-vivo simulation models. Issue 2 (February 2019) - Pafitanis, Georgios; Cooper, Lilli; Hadjiandreou, Michalis; Ghanem, Ali; Myers, Simon
Abstract: Introduction: Microvascular anastomosis with coupler devices has revolutionized microsurgery practice. Couplers are considered easier to apply and offer improved operating time while maintaining success rates. This study aims to map the learning curve, skill acquisition, and decay of novice microsurgeons in performing coupler anastomosis. Methods: Novice microsurgeons performed consecutive coupler applications on a three-layer silastic vessel in two phases. Overall time, total movements, and total path-length were objectively measured and the overall surgical performance was calculated using hand motion analyzer (Dextrous MD, Inition, London, UK). Results: Sixty coupler anastomoses were performed using the synthetic, three-layered silicone vessel by 5 novices, 40 for phase 1, 12 for phase 2 and 8 for phase 3 . During the phase 1 and phase 2 learning curves deliberate practice, the novices required an average of 8 (6–9) and 4 (2–6) consecutive repetitions, respectively, before reaching the experts' performance. There was an average improvement of 69% ( p < 0.001) from their baseline performance during phase I and 37% ( p < 0.001) during phase II. End-product assessment revealed that 4 out of 40 coupler applications during phase 1 (10%), 3 out of 20 during phase 2 (15%), and 1 out of 8 during exit performance-phase 3 (12.5%). During phase 3 end-product assessment with f-cMP, 7 out of 8 arterial and venous coupler anastomoses demonstrated an adequate range of flow measures. Conclusion: This study demonstrated objectively learning curves and skill decay following a suggested coupler application curriculum and quantified objective thresholds for ethical animal model training and safe supervised clinical sessions in the OR.